PENINGKATAN KETRAMPILAN BERBICARA MELALUI MEDIA VLOG TEMATIK BERBASIS KEGIATAN HARIAN SISWA DI SMKS 10 NOVEMBER TAMBUN SELATAN - Margiati; Triyono; Sukini; Hersulastuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the implementation of speaking learning through thematic vlog media based on students’ daily activities and to identify the improvement in students’ learning outcomes among tenth-grade students of SMKS 10 November Tambun Selatan. The research employed a Classroom Action Research (CAR) method, conducted in two cycles consisting of four main stages: planning, action, observation, and reflection. The results showed that the use of thematic vlog media significantly improved students’ speaking skills in both linguistic and non-linguistic aspects. In the linguistic aspect, improvements were observed in vocabulary mastery, sentence accuracy, and pronunciation, while in the non-linguistic aspect, students showed better fluency, confidence, material mastery, and attitude. The average class score increased from 63.9 in the pre-action stage to 70.3 in cycle I and 78.8 in cycle II. Moreover, the percentage of students achieving the minimum mastery criteria (KKM) rose from 19% in the pre-action to 55% in cycle I and 90% in cycle II. These findings indicate that thematic vlog media based on students’ daily activities effectively enhances students’ speaking competence and learning motivation. Therefore, vlog media can serve as an innovative and engaging alternative for teaching Indonesian language, particularly in developing students’ speaking skills at the vocational high school level.